Poor sanitation and transmission of COVID-19 in Brazil - Alves, Mário Ribeiro; Souza, Rita Adriana Gomes de; Caló, Romero dos Santos (São Paulo Medical Journal, 2021)
Coronavirus is a family of viruses that cause respiratory infections. From cases first recorded in China at the end of 2019, a new type of virus in this family, named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was discovered. The disease caused by this virus, COVID-19, was brought into Brazil bypeople in social classes with greater purchasing power, but groups with larger demographic dimensions have tended to become more affected over time. Poor sanitation can generate risky situations and behavior among people who live in spaces with characteristics that limit their quality of life. Installation of piped water in homes and basic education for the population are fundamental measures for disease control, including in relation to COVID-19. In this updating article, the COVID-19 pandemic was analyzed in the context of iniquities in Brazil (comparing these with the situation in other countries). A bibliographic search of texts relating to basic sanitation, socioeconomic development and transmission of COVID-19 in Brazil and worldwide was conducted.